Análise do comportamento e desempenho hídrico das depressões cársticas da região da APA carste Lagoa Santa (MG) - Diógenes Guilherme Pampolini Amaral (2018)
From the unique karst hydrogeology and geomorphology’s perspective the present study aims to investigate the morphometric and hydrogeological features of karst depressions in the Lagoa Santa Enviromental Protection Area (APA) Karst – Minas Gerais, that outcrop predominantly in the pelitic-carbonate rocks from the Sete Lagoas and Serra de Santa Helena Formations, Bambuí Group. These dissolving features play an important role, similar to the watersheds favoring the concentration of meteoric and surface waters giving rise to lagoons and performing water recharge of underground levels. Geoprocessing techniques coupled with remote sensing allowed the detection of 393 karst depressions using the Digital Elevation Model (DEM) through an ALOS PALSAR satellite image. The supervised classification per maximum likelihood algorithm in multispectral images from Landsat 5 TM and Landsat 8 OLI/TIRS satellites, coloured via band composition, showed excellent classification as a result, according to the Kappa Coefficient and Global Accuracy over 90%. This technique identified water mirror areas insides karst depressions over four different hydrological periods, making it a suitable tool to appraise the karst depressions’ hydric behaviour. Similarities and correlations between morphometrics features related to the karst depression’s shape and evolution were verified by analyses and investigations using multivariate statistics. Considering structural patterns (marked by secondary porosity), results from Factorial Analysis and Main components showed that large depressions, with greater depth and significant limestone massif inside, were the ones containing perennial lakes, that they may not dry out completely at the end of the drought period even in the year with exceptional water crisis.